Effect of Gas Metal Arc Welding on Magnetic Response of Ferritic Stainless Steel - Gupta S.K.; Raja A.R.; Vashista M.; Yusufzai M.Z.K. (My University, 2025)
The variation of magnetic Barkhausen noise (MBN) response of different regions of the gas metal arc welded ferritic stainless steel SS409L plate in terms of number of pulses and root mean square value with the variation of MBN analysis parameters (magnetic field intensity and magnetizing frequency) have been investigated in the present work. Five different values of magnetic field intensity 250, 500, 750, 1000 and 1250 Oe at the constant magnetizing frequency of 25 Hz and four different values of magnetizing frequency 10, 20, 30 and 40 Hz at a constant magnetic field intensity of 800 Oe were used as MBN analysis parameters. It was found that MBN response depends upon the magnetic field intensity and magnetizing frequency as well on grain size and microhardness of different regions. © 2020, King Fahd University of Petroleum & Minerals.